PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN, AKUNTABILITAS PUBLIK, DESENTRALISASI DAN SISTEM PENGENDALIAN INTERN TERHADAP KINERJA MANAJEERIAL PEMERINTAHAN DAERAH (Studi Kasus SKPD Kabupaten Bireuen) - Ikhyanuddin Ikhyanuddin (Sekolah Tinggi Pariwisata Mataram, 2021)
This study aims to analyze the effect of budgetary participation, public accountability, decentralization and internal control systems on the managerial performance of local governments in 2020. This type of research is quantitative using secondary data. The population in this study were all SKPDs of Bireun Regency. The sample was selected using a purposive sampling method and obtained 52 SKPDs of Bireuen Regency. The data analysis technique in this study used multiple linear regression analysis and moderated regression analysis were processed using SPSS version 25. The results showed that by means of the t- test of Participation in Budgeting, Public Accountability had an effect on the Managerial Performance of Local Government in SKPD Bireuen Regency in 2020. Decentralization, the Internal Control System has no effect on the Managerial Performance of the Regional Government in the SKPD of Bireun Regency in 2020. The results of the F-test show that Participation in Budgeting, Public Accountability, Decentralization and the Internal Control System have an effect on the Managerial Performance of Local Government in the SKPD of Bireuen Regency in 2020